ADHESIVE FILM, OPTICAL MEMBER COMPRISING THE SAME, AND OPTICAL DISPLAY DEVICE COMPRISING THE SAME

A (meth)acrylic-based adhesive film with controlled shear deformation and high peeling force addresses the challenges of thinness, folding, and adhesion to polyimide films in foldable optical displays, providing reliable adhesion and durability.

JP7617204B2Active Publication Date: 2025-01-17SAMSUNG SDI CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023135563
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-23
Filing Date
2023-08-23
Publication Date
2025-01-17
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

Conventional adhesive films face challenges in achieving thin thickness with low thickness deviation, excellent folding characteristics, and high peeling force against polyimide films, particularly in foldable optical display devices.

Method used

An adhesive film composed of a (meth)acrylic copolymer, (meth)acrylic oligomer, and a curing agent, with specific properties such as a maximum shear deformation rate of 50% or less at 60°C and a peeling force of 600 gf/25 mm (235.4 N/m) or more, is developed to address these issues.

Benefits of technology

The adhesive film achieves a thin, uniform thickness with excellent folding characteristics and high reliability against polyimide films, ensuring consistent adhesion and durability in foldable optical display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617204000003
    Figure 0007617204000003
  • Figure 0007617204000004
    Figure 0007617204000004
  • Figure 0007617204000005
    Figure 0007617204000005
Patent Text Reader

Abstract

To provide an adhesive film having low thickness deviation, excellent folding (foldable) properties and high peeling force to a polyimide-based film while having thin thickness.SOLUTION: There is provided an adhesive film comprising a (meth)acrylic copolymer, a (meth)acrylic oligomer and a curing agent, wherein the maximum value of a shear deformation rate at 60°C is 50% or less and the peeling force to a polyimide-based film at 25°C is 600 gf / 25 mm (235.4 N / m) or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive film, an optical member including the same, and an optical display device including the same. [Background technology]

[0002] As interest in foldable optical display devices increases, adhesive films with excellent foldable properties are also required for adhesive films included in optical display devices. In addition, in light-emitting element panels that emit heat for a long period of time when optical display devices are driven, polyimide-based films are used as base films for heat resistance, so adhesive films with high peel strength against polyimide-based films are required.

[0003] As the demand for thinner optical display devices increases, there is a strong tendency to make adhesive films thinner as well. However, conventional UV-curable adhesive films having foldable properties are manufactured from solvent-free compositions in order to increase UV curing efficiency, and there is a limit to how thin the adhesive film can be made. In addition, since adhesive films are manufactured by applying a composition and then curing it, it is not easy to manufacture an adhesive film with a low thickness deviation when manufacturing a thin adhesive film from a solvent-free composition. Conventional thermosetting adhesive films having foldable properties are known, but there is a limit to how much they can increase the peel strength against polyimide-based films. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-072951 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide an adhesive film which is thin but has a small thickness deviation, has excellent foldable properties, and has a high peel strength to polyimide films.

[0006] Another object of the present invention is to provide an adhesive film which is formed from a thermosetting composition and has excellent foldable properties. [Means for solving the problem]

[0007] According to one embodiment of the present invention, an adhesive film is provided.

[0008] The adhesive film contains a (meth)acrylic copolymer, a (meth)acrylic oligomer, and a curing agent, and the adhesive film has a maximum shear deformation rate of 50% or less at 60°C and a peel strength from a polyimide film of 600 gf / 25 mm (235.4 N / m) or more at 25°C.

[0009] According to another embodiment of the present invention, an optical member is provided.

[0010] The optical member includes the pressure-sensitive adhesive film.

[0011] According to yet another embodiment of the present invention, an optical display device is provided.

[0012] The optical display device includes the above-mentioned pressure-sensitive adhesive film. Effect of the Invention

[0013] According to the present invention, it is possible to provide a pressure-sensitive adhesive film that is thin but has a low thickness deviation, has excellent foldable properties, and has a high peel strength to polyimide films. [Brief description of the drawings]

[0014] [Figure 1]FIG. 2 is a diagram showing the measurement results of the shear deformation rate of an adhesive film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a method for measuring the peel strength of an adhesive film according to one embodiment of the present invention to a polyimide film or a polyethylene terephthalate film. [Diagram 3] 1 is a schematic diagram showing a method for measuring the peel strength of an adhesive film according to one embodiment of the present invention to a glass plate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, each embodiment of the present invention will be described in more detail. However, the technology disclosed in this specification is not limited to each embodiment described herein, and may be embodied in other forms. However, each embodiment described herein is provided to thoroughly and completely disclose the contents, and to fully convey the idea of ​​the present invention to those skilled in the art.

[0016] The terms used herein are merely used to describe each illustrative embodiment and are not intended to limit the present invention. A singular expression includes a plural expression unless it has a clearly different meaning in the context.

[0017] In this specification, "shear deformation rate" is a value measured at 60°C, and means the degree of deformation when a constant shear force is applied to the adhesive film over time. Referring to Figure 1, the deformation rate (strain) of the adhesive film is measured when a constant force is applied to the adhesive film over time under the conditions of the following experimental example. The maximum value of "shear deformation rate" at 60°C means the value at which the shear deformation rate is maximum in the graph shown in Figure 1.

[0018] In this specification, "(meth)acrylic" means acrylic and / or methacrylic.

[0019] In this specification, the "weight average molecular weight (Mw)" is a value determined by gel permeation chromatography using polystyrene standards.

[0020] In this specification, when describing a numerical range, "X to Y" means at least X and at most Y (X≦ and ≦Y).

[0021] The present inventors have provided an adhesive film that is thin but has a low thickness deviation, has excellent folding (foldable) characteristics, and has a high peel strength against a polyimide film. The present inventors have provided an adhesive film formed from a thermosetting composition and has excellent folding (foldable) characteristics. The adhesive film of the present invention may be used as a thermosetting transparent adhesive (OCA) in a folding (foldable) optical display device.

[0022] The adhesive film may have a thickness of 20 μm or less. If the thickness is in this range, the adhesive film provides an ultra-thin thickness, and even when used in a foldable optical display device, the adhesive film can provide a sufficient thinning effect. Specifically, the adhesive film may have a thickness of more than 0 μm and 20 μm or less, or may be 5 μm to 15 μm.

[0023] The adhesive film has a peel strength to a polyimide film at 25°C of 600gf / 25mm (N / m) or more. If the peel strength to a polyimide film at 25°C is in this range, the adhesive film can be reliably adhered to a polyimide film in a foldable optical display device. For example, the peel strength can be measured in a peel test at a peel angle of 180°. test), 600gf / 25mm(235.4N / m), 650gf / 25mm(255.0N / m), 700gf / 25mm(274.6N / m), 750gf / 25mm(294 .3N / m), 800gf / 25mm(313.9N / m), 850gf / 25mm(333.5N / m), 900gf / 25mm(353.1N / m), 950gf / 25mm(372.7N / m) m), 1000gf / 25mm(392.3N / m), 1050gf / 25mm(412.0N / m), 1100gf / 25mm(431.6N / m), 1150gf / 25mm(451.2N / m), 1200gf / 25mm(470.8N / m), 1250gf / 25mm(490.4N / m), 1300gf / 25mm(510.0N / m), 1350gf / 25mm(530.0N / m), 1400gf / 25mm(549.3N / m), 1450gf / 25mm(568.9N / m), 1500gf / 25mm(588.5N / m), 1550gf / 25mm(608.1N / m), 1600gf / 25mm(627.7N / m), 1650gf / 25mm(647.4N / m), 1700gf / 25mm(667.0N / m), 1750gf / 25mm(686.6 N / m), 1800gf / 25mm (706.2N / m), 1850gf / 25mm (725.8N / m), 1900gf / 25mm (745.4N / m), 1950gf / 25mm (765.1N / m), or 2000gf / 25mm (784.7N / m), or may be 600gf / 25mm (235.4N / m) to 2000gf / 25mm (784.7N / m).Here, "high reliability" means that when the adhesive film is applied to a foldable optical display device, the adhesive film does not peel off from the polyimide film at room temperature (e.g., 25°C), high temperature (e.g., 60°C), high temperature and high humidity (e.g., 60°C and 95% relative humidity), and low temperature (e.g., -20°C), providing a folding effect. Note that 1gf / 25mm=0.3924N / m.

[0024] The adhesive film may have a peel strength against a polyimide film at 85°C of 400gf / 25mm (156.9N / m) or more. If the peel strength against a polyimide film at 85°C is in this range, the adhesive film can be highly reliably adhered to the polyimide film in the foldable optical display device. For example, the peel strength may be 400gf / 25mm (156.9N / m), 450gf / 25mm (176.6N / m), 500gf / 25mm (196.2N / m), 550gf / 25mm (215.8N / m), 600gf / 25mm (235.4N / m), 650gf / 25mm (235.4N / m), 700gf / 25mm (235.4N / m), 800gf / 25mm (235.4N / m), 900gf / 25mm (235.4N / m), 1000gf / 25mm (235.4N / m), 1100gf / 25mm (235.4N / m), 1200gf / 25mm (235.4N / m), 1300gf / 25mm (235.4N / m), 1400gf / 25mm (235.4N / m), 1500gf / 25mm (235.4N / m), 1600gf / 25mm (235.4N / m), 1700gf / 25mm (235.4N / m), 1800gf / 25mm (235.4N / m), 1900gf / 25mm (235.4N / m), 200gf / 25mm (235.4N / m), 2 255.0N / m), 700gf / 25mm(274.6N / m), 750gf / 25mm(294.3N / m), 800gf / 25mm(313.9N / m), 850gf / 25mm(333.5N / m), 900gf / 25mm(353.1N / m), 950gf / 25mm(372.7N / m), 1000gf / 25m m(392.3N / m), 1050gf / 25mm(412.0N / m), 1100gf / 25mm(431.6N / m), 1150gf / 25mm(451.2 N / m), 1200gf / 25mm(470.8N / m), 1250gf / 25mm(490.4N / m), 1300gf / 25mm(510.0N / m), 13 It may be 50gf / 25mm (530.0N / m), 1400gf / 25mm (549.3N / m), 1450gf / 25mm (568.9N / m), or 1500gf / 25mm (588.5N / m), or it may be 400gf / 25mm (157.0N / m) to 1500gf / 25mm (588.5N / m).

[0025] The pressure-sensitive adhesive film has a high peel strength against a polyimide-based film at both temperatures of 25° C. and 85° C., and a low ratio of the peel strength against a polyimide-based film between 25° C. and 85° C., and therefore can provide high reliability when applied to an optical display device. In one specific example, the ratio of the peel strength against a polyimide-based film at 85° C. to the peel strength against a polyimide-based film at 25° C. may be 0.55 or more, for example, 0.58 to 1.

[0026] Polyimide-based films have superior flexibility and heat resistance compared to other polymer films, and are widely used in foldable optical display devices as the base film of window films or the base film of panels for optical display devices such as OLED panels. The polyimide-based film may be a film manufactured using a conventional method known to those skilled in the art for manufacturing polyimide-based films. For example, the polyimide-based film may be a film formed by the reaction between an acid dianhydride and a diamine. The acid dianhydride may be pyromellitic dianhydride, benzoquinone tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, etc., and the diamine may be oxydianiline, phenylenediamine, diaminodiphenylmethane, etc.

[0027] The adhesive film of the present invention has a maximum shear deformation rate of 50% or less at 60°C and a thickness deviation of 4 nm or less. In this range, when the adhesive film is applied to a foldable optical display device under a wide range of conditions, the problem of the quality of the screen being reduced due to uneven thickness can be minimized. Here, the "wide range of conditions" can include room temperature (e.g., 25°C), high temperature (e.g., 60°C), high temperature and high humidity (e.g., 60°C and 95% relative humidity), and low temperature (e.g., -20°C). Specifically, the adhesive film may have a maximum shear deformation rate of 1% to 50% at 60°C, more specifically, 10% to 40%. Specifically, the adhesive film may have a thickness deviation of 0 nm to 4 nm.

[0028] The adhesive film may have a storage modulus of 0.2 MPa or less at -20°C, for example, 0.001 MPa to 0.2 MPa, 0.05 MPa to 0.2 MPa, or 0.05 MPa, 0.06 MPa, 0.07 MPa, 0.08 MPa, 0.09 MPa, 0.1 MPa, 0.11 MPa, 0.12 MPa, 0.13 MPa, 0.14 MPa, 0.15 MPa, 0.16 MPa, 0.17 MPa, 0.18 MPa, 0.19 MPa, or 0.2 MPa. If the storage modulus at -20°C is in such a range, it can be promoted to provide excellent folding (foldable) properties under a wide range of conditions.

[0029] The pressure-sensitive adhesive film may have a storage modulus of 0.2 MPa or less, for example, 0.001 MPa to 0.2 MPa, or may have a storage modulus of 0.1 MPa to 0.2 MPa at 25° C. If the storage modulus at 25° C. is within such a range, excellent folding (foldable) properties can be easily provided under a wide range of conditions.

[0030] The adhesive film may have a storage modulus at 60° C. of 0.2 MPa or less, for example, 0.001 MPa to 0.2 MPa, or 0.01 MPa to 0.1 MPa, for example, 0.02 MPa, 0.03 MPa, 0.04 MPa, 0.05 MPa, 0.06 MPa, 0.07 MPa, 0.08 MPa, 0.09 MPa, or 0.1 MPa. If the storage modulus at 60° C. is in such a range, it can be promoted to provide excellent folding (foldable) properties under a wide range of conditions.

[0031] The adhesive film may have a ratio of the storage modulus at -20°C to the storage modulus at 60°C (storage modulus at -20°C:storage modulus at 60°C) of 1:0.1 to 1:0.8, specifically, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, for example, 1:0.2 to 1:0.5. If the storage modulus ratio is in such a range, excellent folding (foldable) properties can be easily provided under a wide range of conditions.

[0032] The adhesive film may have a temperature at which the tan δ value is maximum of 0° C. or lower, specifically, −50° C. to 0° C., −50° C., −45° C., −40° C., −35° C., −30° C., −25° C., −20° C., −15° C., −10° C., −5° C., 0° C., and more specifically, −50° C. to −15° C. If the temperature at which the tan δ value is maximum is within such a range, excellent foldable properties can be easily provided under a wide range of conditions.

[0033] The adhesive film may have a haze of 1% or less, for example, 0% to 1%, in the visible light region, for example, at wavelengths of 380 nm to 780 nm. If the haze is in such a range, the adhesive film can be used in optical display devices.

[0034] The adhesive film may have a peel strength of 600 gf / 25 mm (235.4 N / m) or more from a glass plate at 25° C. If the peel strength from a glass plate at 25° C. is in this range, the adhesive film can be adhered with high reliability to various optical elements of a foldable optical display device. For example, the peel force may be 600gf / 25mm (235.4N / m), 650gf / 25mm (255.0N / m), 700gf / 25mm (274.6N / m), 750gf / 25mm (294.3N / m), 800gf / 25mm (313.9N / m), 850gf / 25mm (333.5N / m), 900gf / 25mm (353.1N / m), 950gf / 25mm (372.7N / m), 1000gf / 25mm (392.3N / m), for example, 600gf / 25mm (235.4N / m) to 1000gf / 25mm (392.3N / m) in a peel test at a peel angle of 90°.

[0035] The adhesive film may have a peel strength of 600 gf / 25 mm (235.4 N / m) or more against a corona-treated polyethylene terephthalate film at a temperature condition of 25° C. If the peel strength against a corona-treated polyethylene terephthalate film at a temperature condition of 25° C. is in this range, the adhesive film can be adhered with high reliability to various optical elements of a foldable optical display device. For example, the peel force in a peel test at a peel angle of 180° may be 600gf / 25mm (235.4N / m), 650gf / 25mm (255.0N / m), 700gf / 25mm (274.6N / m), 750gf / 25mm (294.3N / m), 800gf / 25mm (313.9N / m), 850gf / 25mm (333.5N / m), 900gf / 25mm (353.1N / m), 950gf / 25mm (372.7N / m), or 1000gf / 25mm (392.3N / m), or may be 600gf / 25mm (235.4N / m) to 1000gf / 25mm (392.3N / m).

[0036] The adhesive film may have a peel strength of 400 gf / 25 mm (156.9 N / m) or more from a corona-treated polyethylene terephthalate film at a temperature condition of 85° C. If the peel strength from a corona-treated polyethylene terephthalate film at a temperature condition of 85° C. is in this range, the adhesive film can be adhered with high reliability to various optical elements of a foldable optical display device. For example, the peel strength in a peel test at a peel angle of 180° is 400gf / 25mm (156.9N / m), 450gf / 25mm (176.6N / m), 500gf / 25mm (196.2N / m), 550gf / 25mm (215.8N / m), 600gf / 25mm (235.4N / m), 650gf / 25mm (255.0N / m), 700gf / 25mm (274.6N / m), 750gf / It may be 25mm (294.3N / m), 800gf / 25mm (313.9N / m), 850gf / 25mm (333.5N / m), 900gf / 25mm (353.1N / m), 950gf / 25mm (372.7N / m), or 1000gf / 25mm (392.3N / m), or it may be 400gf / 25mm (156.9N / m) to 1000gf / 25mm (392.3N / m).

[0037] The adhesive film includes a (meth)acrylic copolymer, a (meth)acrylic oligomer, and a curing agent, and the curing agent may be an isocyanate-based curing agent. The adhesive film may further include a metal chelate-based curing agent. The adhesive film may further include a silane coupling agent. In one specific example, the adhesive film may be a thermally cured product of the composition.

[0038] In one embodiment, the adhesive film may be formed from a composition including a (meth)acrylic copolymer, a (meth)acrylic oligomer, and a curing agent. The curing agent may be a trifunctional or higher isocyanate-based curing agent. The composition may further include a metal chelate-based curing agent. The composition may further include a silane coupling agent. In one embodiment, the adhesive film may include a thermally cured product of the composition.

[0039] The (meth)acrylic copolymer can react with the (meth)acrylic oligomer and curing agent described below to form the matrix of the adhesive film, thereby helping to provide the peel force and shear deformation rate.

[0040] The (meth)acrylic copolymer may be a copolymer of a monomer mixture containing a (meth)acrylic monomer having an alkyl group.

[0041] As the (meth)acrylic monomer having an alkyl group, one selected from (meth)acrylic monomers having a linear or branched alkyl group having 1 to 20 carbon atoms may be used. The (meth)acrylic monomer having a linear or branched alkyl group having 1 to 20 carbon atoms is a (meth)acrylic acid ester having an alkyl group having 1 to 20 carbon atoms at the ester moiety, and may include, for example, at least one selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, iso-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, iso-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate.

[0042] The (meth)acrylic monomer having an alkyl group may be contained in the monomer mixture at a content of 90% by mass or more, specifically 95% by mass to 100% by mass, and more specifically 99% by mass to 100% by mass. If the content of the (meth)acrylic monomer having an alkyl group is within such a range, the matrix of the adhesive film can be easily formed.

[0043] The (meth)acrylic copolymer may be a copolymer of a monomer mixture containing a (meth)acrylic monomer having a homopolymer glass transition temperature of -50°C or less. The (meth)acrylic monomer having a homopolymer glass transition temperature of -50°C or less lowers the glass transition temperature of the (meth)acrylic copolymer, and thus the shear deformation rate and peel strength of the present invention can be easily achieved. The (meth)acrylic monomer may have a homopolymer glass transition temperature of -80°C to -50°C, specifically. The "glass transition temperature of the homopolymer of the (meth)acrylic monomer" can be measured by a conventional method known to those skilled in the art, or can be obtained by referring to a commercial catalog.

[0044] In one specific example, the (meth)acrylic monomer having a homopolymer glass transition temperature of -50°C or lower may be contained in the monomer mixture at a content of 90% by mass or more, specifically 95% by mass to 100% by mass, and more specifically 99% by mass to 100% by mass. If the content of the (meth)acrylic monomer having a homopolymer glass transition temperature of -50°C or lower is within such a range, the glass transition temperature of the (meth)acrylic copolymer can be easily lowered.

[0045] The (meth)acrylic monomer having a homopolymer glass transition temperature of -50°C or lower may be a (meth)acrylic monomer having the above-mentioned alkyl group, and the monomer mixture may contain one or more types, preferably two or more types, of the (meth)acrylic monomer having a homopolymer glass transition temperature of -50°C or lower.

[0046] In one specific example, the (meth)acrylic monomer having an alkyl group may be a mixture of a first monomer having a homopolymer glass transition temperature of -50°C or less, and a second monomer having a homopolymer glass transition temperature of -50°C or less and different from the first monomer. The first monomer may have a homopolymer glass transition temperature different from that of the second monomer, preferably lower than that of the second monomer. When the total number of moles of the first monomer and the second monomer is taken as 100, the molar ratio of the first monomer to the second monomer in the mixture (first monomer:second monomer) may be 40:60 to 70:30. When the molar ratio of the first monomer to the second monomer is within such a range, the glass transition temperature of the (meth)acrylic copolymer can be easily lowered. For example, the first monomer may be n-butyl acrylate, etc. The second monomer may be 2-ethylhexyl acrylate, etc.

[0047] The monomer mixture may not contain at least one of the (meth)acrylic monomers having a crosslinkable functional group, or may contain a small amount of the at least one of the (meth)acrylic monomers having a crosslinkable functional group. However, it may further contain at least one of the (meth)acrylic monomers having a crosslinkable functional group within a range that does not affect the effects of the present invention. Specifically, the content of the (meth)acrylic monomer having a crosslinkable functional group in the monomer mixture is 1% by mass or less, for example, 0% by mass, 0.01% by mass, 0.02% by mass, 0.03% by mass, 0.04% by mass, 0.05% by mass, 0.06% by mass, 0.07% by mass, 0.08% by mass, 0.09% by mass, 0.1% by mass, 0.15% by mass, 0.2% by mass, 0.25% by mass, 0.3% by mass, 0.4% by mass, 0.5% by mass, 0.6% by mass, 0.7% by mass, 0.8% by mass, 0.9% by mass, 0.1% by mass, 0.2 ...8% by mass, 0.9% by mass, 0.1% by mass, 0.1% by mass, 0.2% by mass, 0.3% by mass, 0.4% by mass, 0.5% by mass, 0 The content may be 0.35 mass%, 0.4 mass%, 0.45 mass%, 0.5 mass%, 0.55 mass%, 0.6 mass%, 0.65 mass%, 0.7 mass%, 0.75 mass%, 0.8 mass%, 0.85 mass%, 0.9 mass%, 0.95 mass%, or 1 mass%, or may be 0 mass% to 1 mass%, more than 0 mass% and up to 0.5 mass%, or more than 0 mass% and up to 0.05 mass%.

[0048] The (meth)acrylic monomer having a crosslinkable functional group may be at least one selected from the group consisting of a (meth)acrylic monomer having a hydroxyl group, a (meth)acrylic monomer having a carboxylic acid group, a (meth)acrylic monomer having an amino group, and a (meth)acrylic monomer having an amide group.

[0049] As the (meth)acrylic monomer having a hydroxyl group (hydroxy group), one selected from (meth)acrylic monomers having a linear or branched alkyl group having 1 to 20 carbon atoms and one or more hydroxyl groups (hydroxy groups) may be used. For example, the (meth)acrylic monomer having a hydroxyl group (hydroxy group) is a (meth)acrylic acid ester having an alkyl group having 1 to 20 carbon atoms and having one or more hydroxyl groups (hydroxy groups) at the ester moiety, and can include at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, 1-chloro-2-hydroxypropyl (meth)acrylate, diethylene glycol mono(meth)acrylate, 2-hydroxy-3-phenyloxypropyl (meth)acrylate, 4-hydroxycyclopentyl (meth)acrylate, and 4-hydroxycyclohexyl (meth)acrylate.

[0050] The (meth)acrylic monomer having a carboxylic acid group (carboxy group) may be (meth)acrylic acid or the like.

[0051] The (meth)acrylic monomer having an amino group can include alkylamino(meth)acrylate, dialkylamino(meth)acrylate, and the like.

[0052] The (meth)acrylic monomer having an amide group can include (meth)acrylamide, (meth)acrylamide having an alkyl group such as dimethyl(meth)acrylamide, and the like.

[0053] The (meth)acrylic copolymer may be a random copolymer, a block copolymer or an alternating copolymer, but is preferably a random type (meth)acrylic copolymer.

[0054] The (meth)acrylic copolymer may have a glass transition temperature of −50° C. or lower, for example, −70° C., −65° C., −60° C., −55° C., −50° C., or −70° C. to −50° C. If the glass transition temperature of the (meth)acrylic copolymer is within such a range, the shear deformation ratio and peel strength of the present invention can be easily achieved.

[0055] The (meth)acrylic copolymer may have a weight average molecular weight of 800,000 g / mol or more, for example, 800,000 g / mol, 900,000 g / mol, 1,000,000 g / mol, 1,100,000 g / mol, 1,200,000 g / mol, 1,300,000 g / mol, 1,400,000 g / mol, 1,500,000 g / mol, preferably 80 g / mol to 1,500,000 g / mol, more preferably 1,000,000 g / mol to 1,300,000 g / mol. If the weight average molecular weight of the (meth)acrylic copolymer is in such a range, the shear deformation rate and peel force of the present invention can be easily achieved. The above "weight average molecular weight" may be determined as a polystyrene equivalent value using gel permeation chromatography.

[0056] The (meth)acrylic copolymer may have a polydispersity index (PDI, weight average molecular weight / number average molecular weight) of 3 to 10, for example, 3 to 5. When the polydispersity index of the (meth)acrylic copolymer is within this range, the effects of the present invention can be easily realized.

[0057] The (meth)acrylic copolymer may have an acid value of 0.5 mgKOH / g or less, specifically 0 mgKOH / g to 0.5 mgKOH / g, and more specifically 0 mgKOH / g. If the acid value of the (meth)acrylic copolymer is in this range, corrosion can be suppressed when the (meth)acrylic copolymer comes into contact with a metal-containing optical element.

[0058] The (meth)acrylic copolymer may be produced by polymerizing the above-mentioned monomer mixture by a conventional polymerization method. The polymerization method may include conventional methods known to those skilled in the art. For example, the (meth)acrylic copolymer may be produced by adding an initiator to the monomer mixture, followed by conventional copolymerization, such as suspension polymerization, emulsion polymerization, solution polymerization, etc. The polymerization temperature may be 60°C to 70°C, and the polymerization time may be 6 hours to 8 hours. As the initiator, a conventional initiator including an azo-based polymerization initiator; and / or a peroxide such as benzoyl peroxide or acetyl peroxide, etc. may be used.

[0059] The (meth)acrylic oligomer provides the shear deformation ratio of the present invention and can promote an increase in the peel strength of the adhesive film relative to the polyimide film.

[0060] Since the (meth)acrylic oligomer has a higher glass transition temperature than the (meth)acrylic copolymer, the pressure-sensitive adhesive film can have an appropriate storage modulus at room temperature.

[0061] In one specific example, the (meth)acrylic oligomer may have a glass transition temperature of 60° C. or less, for example, less than 60° C., 20° C. to 60° C., for example, 30° C. to 50° C., for example, 30° C. to 40° C. If the glass transition temperature is within such a range, it is possible to promote an increase in the peel strength of the pressure-sensitive adhesive film relative to the polyimide film while decreasing the storage modulus at low temperatures.

[0062] The (meth)acrylic oligomer has a lower weight average molecular weight than the (meth)acrylic copolymer. For example, the (meth)acrylic oligomer may have a weight average molecular weight of 3,000 g / mol to 50,000 g / mol, for example, 10,000 g / mol to 40,000 g / mol. If the weight average molecular weight of the (meth)acrylic oligomer is in this range, it is possible to promote the increase in the peeling force of the adhesive film against the polyimide film while reducing the storage modulus at low temperatures.

[0063] The (meth)acrylic oligomer can have a hydroxyl group as a crosslinkable functional group. This can enhance the reaction with the curing agent and the peeling force even when a (meth)acrylic copolymer with a low content of crosslinkable functional groups is used. The hydroxyl group can be provided by using the above-mentioned (meth)acrylic monomer having a hydroxyl group when producing the (meth)acrylic oligomer.

[0064] The (meth)acrylic oligomer may contain, as a main constituent unit, a constituent unit derived from a (meth)acrylic monomer having a homopolymer glass transition temperature of 90° C. or higher, for example, a homopolymer glass transition temperature of 100° C. to 120° C. If the glass transition temperature of the homopolymer of the (meth)acrylic monomer is in this range, it is possible to prevent the storage modulus of the adhesive film at high temperatures from becoming excessively high, and the above-mentioned range of glass transition temperature can be ensured. For example, the (meth)acrylic monomer may be a monofunctional (meth)acrylic monomer, specifically, at least one selected from the group consisting of methyl methacrylate, methacrylic acid, and tert-butyl methacrylate, but is not limited thereto. The "main constituent unit" means that the corresponding monomer is contained in an amount of 50% by mass or more, or 60% by mass or more, of the entire constituent units of the (meth)acrylic oligomer.

[0065] The (meth)acrylic oligomer may further contain a constituent unit derived from a (meth)acrylic monomer having a homopolymer glass transition temperature of 50° C. or lower, for example, a glass transition temperature of −60° C. to 0° C. For example, the (meth)acrylic monomer having a homopolymer glass transition temperature of 50° C. or lower may be n-butyl acrylate. The (meth)acrylic oligomer may be produced by polymerizing the monomer mixture by a conventional polymerization method. The polymerization method may include conventional methods known to those skilled in the art. For example, the (meth)acrylic oligomer may be produced by adding an initiator to the monomer mixture and then performing conventional polymerization, such as suspension polymerization, emulsion polymerization, solution polymerization, etc. In this case, the polymerization temperature and polymerization time may be adjusted within a range that provides the above-mentioned weight average molecular weight and glass transition temperature. As the initiator, conventional initiators including azo-based polymerization initiators and / or peroxides such as benzoyl peroxide or acetyl peroxide can be used.

[0066] The (meth)acrylic oligomer may be contained in an amount of 5 parts by mass or less, for example, more than 0 parts by mass and 5 parts by mass or less, 0.001 parts by mass to 0.1 parts by mass, or 0.01 parts by mass to 0.1 parts by mass, relative to 100 parts by mass of the (meth)acrylic copolymer. If the content of the (meth)acrylic oligomer is within such a range, the shear deformation rate of the present invention can be obtained, and the peeling force of the adhesive film relative to the polyimide film can be improved.

[0067] The curing agent can promote a decrease in the shear deformation rate of the adhesive film by increasing the crosslinking density of the adhesive film while increasing the peel strength of the adhesive film.

[0068] In one specific example, a trifunctional or higher isocyanate-based curing agent may be used as the curing agent. The trifunctional or higher isocyanate-based curing agent can remarkably and easily reduce the shear deformation rate of the adhesive film by increasing the crosslinking density of the adhesive film while increasing the peeling force of the adhesive film compared to a bifunctional isocyanate-based curing agent.

[0069] The trifunctional or higher isocyanate-based curing agent can be any curing agent having three or more isocyanate groups (NCO). Specifically, it can include trifunctional isocyanurates of isocyanate-based compounds, adducts with polyol compounds such as trimethylolpropane, or biuret compounds. The isocyanate-based compounds include aromatic diisocyanates such as 2,4-tolylene diisocyanate (2,4-TDI), 2,6-tolylene diisocyanate (2,6-TDI), 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 1,4-phenylene diisocyanate, xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), tolidine diisocyanate (TODI), and 1,5-naphthalene diisocyanate (NDI). Isocyanates may include aliphatic diisocyanates such as hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate (TMHDI), lysine diisocyanate, and norbornane diisocyanate methyl (NBDI); alicyclic diisocyanates such as transcyclohexane-1,4-diisocyanate, isophorone diisocyanate (IPDI), H6-XDI (hydrogenated XDI), and H12-MDI (hydrogenated MDI); or carbodiimide-modified diisocyanates of the above diisocyanates. For example, a trifunctional or higher isocyanate-based curing agent may be a trifunctional isocyanate-based adduct between toluene diisocyanate and trimethylolpropane.

[0070] The curing agent, for example, a trifunctional or higher isocyanate-based curing agent, may be contained in an amount of 1 part by mass or less, for example, more than 0 part by mass and 1 part by mass or less, 0.001 part by mass to 1 part by mass, 0.001 part by mass to 0.5 part by mass, or 0.001 part by mass to 0.1 part by mass, relative to 100 parts by mass of the (meth)acrylic copolymer. If the amount of the trifunctional or higher isocyanate-based curing agent contained is within such a range, the shear deformation rate can be easily ensured while ensuring the peel strength of the adhesive film.

[0071] The above composition may further contain a metal chelate-based curing agent as a curing agent.

[0072] The metal chelate-based curing agent acts as a curing catalyst to increase the curing speed when the composition is thermally cured.

[0073] The metal chelate curing agent is a curing agent composed of a metal and a chelate bond, and may include a conventional curing agent known to those skilled in the art. In one specific example, the metal chelate curing agent may include a curing agent having a metal and two or more chelate bonds, for example, a curing agent having a metal and 3 to 6 chelate bonds. For example, examples of the metal include aluminum, zirconium, titanium, cobalt, etc., and preferably aluminum. For example, ligands forming chelate bonds include acetylacetonate, ethyl acetoacetate, etc., but are not limited thereto. Specifically, the metal chelate curing agent may include at least one selected from the group consisting of acetylacetonate aluminate, aluminum tris(acetylacetonate), aluminum tris(ethyl acetoacetate), aluminum bis(acetoacetate), zirconium tris(acetylacetonate), and cobalt tris(acetylacetonate), but are not limited thereto.

[0074] The metal chelate curing agent may be contained in an amount of 5 parts by mass or less, for example, 0 parts by mass or more and 5 parts by mass or less, more than 0 parts by mass or more and 5 parts by mass or less, 0.001 parts by mass to 5 parts by mass, 0.001 parts by mass to 1 part by mass, or 0.001 parts by mass to 1 part by mass, relative to 100 parts by mass of the (meth)acrylic copolymer. If the content of the metal chelate curing agent is within such a range, the thermal curing rate of the adhesive film can be increased.

[0075] The above composition, i.e., the pressure-sensitive adhesive film, may further contain a silane coupling agent.

[0076] Silane coupling agent can further increase the peeling force of adhesive film. Silane coupling agent can include the usual silane coupling agent known to those skilled in the art. For example, silane coupling agent includes epoxy group-containing silane coupling agent such as glycidoxypropyltrimethoxysilane, glycidoxypropylmethyldimethoxysilane, etc., but is not limited thereto.

[0077] The silane coupling agent may be contained in an amount of 0.01 to 5 parts by mass relative to 100 parts by mass of the (meth)acrylic copolymer. If the content of the silane coupling agent is within this range, an effect of improving the peel strength can be obtained.

[0078] The composition may further include a solvent. The solvent can make the surface of the adhesive film uniform when the adhesive film is made from the composition to a thin thickness, particularly a thickness of 20 μm or less. As the solvent, any ordinary solvent known to those skilled in the art can be used without limitation. For example, the solvent may be an organic solvent such as ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, etc., but is not limited thereto. The composition may have a solid content of 50% by mass or less, for example, 20% by mass or less.

[0079] The composition, i.e., the adhesive film, may further include an additive. The additive may provide additional functions to the adhesive film. Specifically, the additive may include at least one selected from the group consisting of a UV absorber, a reaction inhibitor, an adhesion improver, a thixotropic agent, a conductivity imparting agent, a dye adjuster, a stabilizer, an antioxidant, a leveling agent, and an antistatic agent, but is not limited thereto. The content of the additive in the composition, i.e., the adhesive film, may be appropriately selected within a range that does not affect the effects of the present invention.

[0080] The adhesive film may be produced by thermally curing the above composition, preferably a composition containing a solvent. For example, the adhesive film may be produced by applying the composition to a release film in a predetermined thickness, drying the composition, and removing the solvent to produce a coating film, and then treating the coating film under thermal curing conditions. The thermal curing conditions may mean that the coating film is heat-treated at 90°C to 120°C for 1 minute to 1 hour.

[0081] An optical member according to one embodiment of the present invention will now be described.

[0082] The optical member includes an optical film and an adhesive film formed on at least one surface of the optical film, and the adhesive film includes an adhesive film according to an embodiment of the present invention. Therefore, the optical member has good bending and / or folding properties and can be used in a foldable display device.

[0083] In one embodiment, the optical film provides a certain optical function in a display device, such as polarization, optical compensation, display image quality improvement, and / or electrical conductivity. Examples of the optical film include window films, windows, polarizing plates, color filters, retardation films, elliptical polarizing films, reflective polarizing films, anti-reflection films, compensation films, brightness enhancement films, alignment films, light diffusion films, glass shatterproof films, surface protection films, OLED element barrier layers, plastic LCD substrates, transparent electrode films including ITO (indium tin oxide), FTO (fluorinated tin oxide), AZO (aluminum doped zinc oxide), CNT (carbon nanotube), Ag nanowires, graphene, etc. The method for manufacturing the optical film can be easily manufactured by a person having ordinary skill in the art to which the present invention belongs.

[0084] For example, a touch panel can be formed by attaching a window or optical film to a touch pad using an adhesive film, or an adhesive film can be applied to a conventional polarizing film.

[0085] In another embodiment, the optical film is an optically transparent optical film, and the optical member including the optical film and the adhesive film can function as a support layer of the display element. For example, the display element can include a window film, etc. The window film can include the optical member and a window coating layer (e.g., a silicon-based coating layer) formed on the optical member. Specifically, the optical film has a total light transmittance of 90% or more in the visible light region, and may be a film formed of one or more resins selected from cellulose resins including triacetyl cellulose, polyester resins including polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polybutylene naphthalate, etc., polycarbonate resins, polyimide resins, polystyrene resins, polyacrylate resins including polymethyl methacrylate, etc., cyclic olefin polymer resins, acrylic resins, and polyamide resins. The optical film may have a thickness of 10 μm to 100 μm, specifically 20 μm to 75 μm, and more specifically 30 μm to 50 μm. If the thickness of the optical film is within this range, the optical film can be used as a support layer for a display element.

[0086] The optical member may be a two-layer optical member including an optical film and an adhesive film formed on one side of the optical film, or a three-layer or more film laminate including two or more optical films, at least two of which are laminated with the adhesive film of the present invention.

[0087] The optical display device of the present invention includes the pressure-sensitive adhesive film of the present invention.

[0088] The optical display device may include a light emitting device display device, such as an organic light emitting device display device, a liquid crystal display device, etc. The optical display device may include a flexible display device, but may also include a non-flexible display device. EXAMPLES

[0089] The present invention will be described in more detail with reference to the following preferred examples, which are provided only to facilitate understanding of the present invention and are not intended to limit the scope of the present invention.

[0090] Example 1 A (meth)acrylic binder was produced by polymerizing 100 parts by weight of a monomer mixture containing 50 parts by weight of n-butyl acrylate (n-BA), 49 parts by weight of 2-ethylhexyl acrylate (2-EHA), and 1 part by weight of 4-hydroxybutyl acrylate (4-HBA).

[0091] A composition having a solid content of 20 mass% was produced by mixing 100 parts by mass of the (meth)acrylic binder produced above, 0.08 parts by mass of the (meth)acrylic oligomer 1, 0.03 parts by mass of a trifunctional isocyanate curing agent, 0.05 parts by mass of a metal chelate curing agent, and 0.05 parts by mass of a silane coupling agent based on the solid content, and adding ethyl acetate, which is an organic solvent, as a solvent.

[0092] The composition obtained above was applied to a first release film (light-thin release film) made of PET at a predetermined thickness and then dried to produce a coating film having a thickness of 15 μm after drying. This coating film was covered with a second release film (medium-thin release film) made of PET, and the coating film was dried at 100° C. for 3 minutes to produce an adhesive sheet in which an adhesive film having a thickness of 15 μm exists between the first release film and the second release film.

[0093] (Examples 2 to 3) An adhesive film was produced in the same manner as in Example 1, except that the types of (meth)acrylic binder and (meth)acrylic oligomer in Example 1 were changed as shown in Table 1 below, and the content of each component in the composition was changed as shown in Table 1 below. In Table 1 below, the unit of the content of each component is parts by mass, and "-" means that the corresponding component is not included.

[0094] (Comparative Examples 1 to 5) In Example 1, the types of (meth)acrylic binder and (meth)acrylic oligomer were changed as shown in Table 1 below, and the contents of each component in the composition were changed as shown in Table 1 below. Except for this, an adhesive film was produced in the same manner as in Example 1.

[0095] Comparative Example 6 100 parts by mass of a monomer mixture containing 20 parts by mass of 4-hydroxybutyl acrylate (4-HBA) and 80 parts by mass of 2-ethylhexyl acrylate (2-EHA) and 0.03 parts by mass of Omnirad (registered trademark) 651 (2,2-dimethoxy-2-phenylacetophenone, manufactured by IGM Resins BV) as an initiator were thoroughly mixed in a reactor. After replacing the dissolved oxygen in the reactor with nitrogen gas, the mixture was partially polymerized by irradiating with ultraviolet light using a low-pressure mercury lamp to produce a viscous liquid having a viscosity of 5,000 mPa·s at 25°C. 0.5 parts by mass of Ominirad (registered trademark) 184 (1-hydroxycyclohexyl phenyl ketone, manufactured by IGM Resins BV) as an initiator was added to the viscous liquid and mixed to produce a solventless pressure-sensitive adhesive composition. The pressure-sensitive adhesive composition was applied to a PET (polyethylene terephthalate) film, which is a release film, and the adhesive composition was irradiated with ultraviolet light at 2000 mJ / cm. 2 An adhesive sheet consisting of an adhesive film (thickness 15 μm) and a PET film was produced by irradiating the adhesive film with an amount of light of 15 μm.

[0096] The configurations of the pressure-sensitive adhesive films of the Examples and Comparative Examples are shown in the following Table 1. The pressure-sensitive adhesive films of the Examples and Comparative Examples were evaluated for the physical properties shown in the following Table 2.

[0097] (1) Thickness deviation of adhesive film (unit: nm): For an adhesive sheet having a 15 μm thick adhesive film manufactured in the examples and comparative examples between a first release film made of PET and a second release film made of PET, the thickness (thickness 1) was measured in the entire in-plane direction using a thickness measuring device (ID-C112X, manufactured by Mitutoyo Corporation). Then, the thickness (thickness 2) of the first release film and the thickness (thickness 3) of the second release film were measured in the same manner. After determining the maximum and minimum values ​​when (thickness 1-thickness 2-thickness 3) was calculated, (maximum value-minimum value) was taken as the thickness deviation.

[0098] (2) Peeling force against polyimide (PI) film (unit: gf / 25mm, N / m): The adhesive sheets of the examples and comparative examples were cut into a rectangle of 100mm length x 25mm width, and then the first release film made of PET was peeled off. Next, an adhesive film was placed on the surface of a polyimide film (GL200A, manufactured by SKC Kolon, 150mm length x 25mm width x 50μm thickness), and the second release film made of PET was peeled off and placed on a polyimide film (GL200A, manufactured by SKC Kolon, 150mm length x 25mm width x 50μm thickness), and adhered with a 2kg hand roller to produce a test piece in which the polyimide film, adhesive film, and polyimide film were laminated in this order, as shown in FIG. 2(a). The prepared test specimen was autoclaved at 3.5 bar (0.35 MPa) and 50°C for 1000 seconds, and then fixed in a TA.XT-Plus Texture Analyzer (Stable Micro System). Using the TA.XT-Plus Texture Analyzer, the polyimide film on one side was fixed and the polyimide film on the other side was pulled at a peel angle of 180° and a peel speed of 300 mm / min at 25°C or 85°C as shown in Figure 2(b), and the T-peel peel strength at which the adhesive film was peeled off from the polyimide film was measured.

[0099] (3) Peel force against polyethylene terephthalate (PET) film (unit: gf / 25mm, N / m): Instead of the polyimide film in (2) above, a corona-treated PET release film (corona treatment conditions: corona treatment twice with 78 doses per discharge (total dose: 156 doses)) was used, and a test piece was produced in which the corona-treated PET release film, the adhesive film, and the corona-treated PET release film were laminated in this order. Using this test piece, the peel strength was measured in the same manner as in (2) above at 25°C or 85°C under the conditions of a peel angle of 180° and a peel speed of 300mm / min, at which the adhesive film was peeled off from the corona-treated PET release film.

[0100] (4) Peel strength against glass plate (unit: gf / 25mm, N / m): A glass plate (soda lime glass plate) was used instead of a polyimide film to prepare a test specimen laminated in the order of glass plate-adhesive film-corona treated PET release film as shown in (a) of Figure 3. Using this test specimen, the peel strength was measured at 25°C under the conditions of a peel angle of 90° and a peel speed of 300mm / min, where the adhesive film was peeled from the glass plate, as shown in (b) of Figure 3.

[0101] (5) Shear deformation rate (unit: %): The PET films on both sides were released from the adhesive sheets of the examples and comparative examples to obtain adhesive films (length x width x thickness: 100 mm x 25 mm x 15 μm). A cylindrical test piece (thickness: 400 μm, diameter: 8 mm) having an upper surface and a lower surface was produced by stacking multiple adhesive films and punching the laminate with a punching machine with a diameter of 8 mm.

[0102] The upper and lower surfaces of the cylindrical test piece were attached to the upper and lower jigs of a rheometer (TA, DHR3), a dynamic viscoelasticity measuring device, so that they could be engaged with each other. The chamber temperature was set to 60°C, the axial force was set to 1N, and the torque was set to 2000Pa. The time was set to 600 seconds, and then the force was applied for 600 seconds (600-second stress). After the force was removed for 600 seconds (600-second release), the deformation rate at the stress of 600 seconds became the maximum deformation rate, and this value was obtained as the shear deformation rate. When the shear deformation rate is measured, the deformation rate over time can be obtained, which has the shape of a graph in Figure 1. In Figure 1, the X-axis is time (unit: seconds) and the Y-axis is shear deformation rate (unit:%).

[0103] (6) Storage modulus (unit: MPa): After peeling off two release films from the adhesive sheets produced in the examples and comparative examples, multiple adhesive films were laminated to prepare samples with a thickness of 500 μm. The adhesive film samples were used as test pieces by punching the laminate with a punching machine with a diameter of 8 mm. Using a rheometer (TA, DHR3), a dynamic viscoelasticity measuring device, the storage modulus was measured under conditions of 1% deformation rate and 1 Hz in the temperature range of -50°C to 100°C at a temperature rise rate of 5°C / min in a temperature sweep test mode. The storage modulus was measured at -20°C and 60°C.

[0104] (7) Temperature at which tan δ is maximum (unit: °C, tan δ MAX): The storage modulus and loss modulus were determined in the same manner as in (6). After obtaining the tan δ value as the ratio between the storage modulus and the loss modulus, the temperature at which the tan δ value is maximum was determined.

[0105] (8) Folding properties at low temperature: In the adhesive sheets produced in the examples and comparative examples, the release films on both sides were separated to obtain adhesive films. The adhesive film was placed between two corona-treated polyethylene terephthalate (PET) films having a thickness of 50 μm, the corona-treated surface of the PET film was brought into contact with the adhesive film, and the film was attached with a roller. The film was then aged at room temperature for 12 hours, and cut to a size of width x length (70 mm x 140 mm) to produce a test specimen. The cut test specimen was fixed to a bending evaluation device (CFT-200, Covotech) using an adhesive (4965, Tesa), and the test specimen was repeatedly folded at a rate of 30 cycles per minute at -20°C in the length (140 mm) to a curvature radius of 3 mm (bending, bending the adhesive film in half once and then spreading it out is called one cycle). When bending was repeated as one cycle, the number of cycles at which cracks first appeared in the polyethylene terephthalate film was measured with the naked eye. An adhesive film with a large number of initial cycles means that the stress of the polyethylene terephthalate film caused by bending can be easily relaxed. If the initial cycle number was 100,000 or more, it was judged as OK, and if it was less than 100,000, it was judged as NG.

[0106] The configurations of the examples and comparative examples are shown in Table 1 below, and the results of the above evaluations are shown in Table 2 below.

[0107] [Table 1]

[0108] [Table 2]

[0109] The components in Table 1 above are as follows: (Meth)acrylic oligomer 1: manufactured by Saiden; an oligomer formed from 4-hydroxybutyl acrylate, methyl methacrylate, methacrylic acid and n-butyl acrylate (Meth)acrylic oligomer 2: Saiden; an oligomer formed from 4-hydroxybutyl acrylate, methyl methacrylate, methacrylic acid and tert-butyl methacrylate Trifunctional NCO-based hardener: TDI (toluene diisocyanate)-TMP (trimethylolpropane) modified adduct, manufactured by Saiden Bifunctional NCO-based hardener: HDI-based, manufactured by NCI, hexamethylene diisocyanate-based hardener Metal chelate-based hardener: Saiden, aluminum chelate-based hardener Silane coupling agent: Saiden, 3-glycidoxypropyltrimethoxysilane.

[0110] As shown in Table 2 above, the adhesive film of the present invention was thin but had a low thickness deviation, was formed from a thermosetting composition, and had excellent folding (foldable) properties. The adhesive film of the present invention had a high peel strength against a polyimide-based film, so although not shown in Tables 1 and 2 above, it is expected that the adhesive film of the present invention can be highly reliably adhered to a polyimide-based film in a folding (foldable) optical display device.

[0111] However, the adhesive film of Comparative Example 6, which was manufactured using a conventional photocuring method, had a large deviation in thickness when manufactured to be thin. The adhesive films of Comparative Examples 1 to 5, which do not satisfy the configuration of the present invention, had peel strength against polyimide-based films of less than 600 gf / 25 mm (235.4 N / m), and therefore are expected to have low reliability against polyimide-based films in foldable optical display devices, although this is not shown in Tables 1 and 2 above.

[0112] Simple modifications and variations of the present invention can be easily implemented by those having ordinary skill in the art, and all such modifications and variations can be considered to be included within the scope of the present invention.

Claims

1. A pressure-sensitive adhesive film obtained by curing a composition containing a (meth)acrylic copolymer, a (meth)acrylic oligomer, and a curing agent, The (meth)acrylic copolymer has a weight average molecular weight of 800,000 g / mol to 1,500,000 g / mol and a glass transition temperature of −70° C. to −50° C.; The (meth)acrylic oligomer has a weight average molecular weight of 3,000 g / mol to 50,000 g / mol and a glass transition temperature of 30° C. to 50° C.; The curing agent includes a trifunctional or higher isocyanate-based curing agent, the content of the (meth)acrylic oligomer is more than 0 parts by mass and 0.12 parts by mass or less with respect to 100 parts by mass of the (meth)acrylic copolymer, the content of the tri- or higher functional isocyanate-based curing agent is more than 0 part by mass and 1 part by mass or less relative to 100 parts by mass of the (meth)acrylic copolymer, The pressure-sensitive adhesive film has a maximum shear deformation rate of 50% or less at 60°C and a peel strength from a polyimide film of 600 gf / 25 mm (235.4 N / m) or more at 25°C.

2. The pressure-sensitive adhesive film according to claim 1, wherein the pressure-sensitive adhesive film has a peel strength from the polyimide film at 85°C of 400 gf / 25 mm (156.9 N / m) or more.

3. The adhesive film according to claim 1 , wherein the adhesive film has a thickness deviation of 4 nm or less.

4. The pressure-sensitive adhesive film according to claim 1, wherein the pressure-sensitive adhesive film has a storage modulus of 0.2 MPa or less at -20°C.

5. The pressure-sensitive adhesive film has a ratio of the storage modulus at -20 ° C. to the storage modulus at 60 ° C. (storage modulus at -20 ° C.: storage modulus at 60 ° C.) of 1:0.1 to 1:0.

8. The pressure-sensitive adhesive film according to claim 1.

6. The (meth)acrylic copolymer is a copolymer of a monomer mixture containing two or more (meth)acrylic monomers having alkyl groups each having a different homopolymer glass transition temperature. The pressure-sensitive adhesive film according to claim 1 .

7. The pressure-sensitive adhesive film according to claim 6, wherein the (meth)acrylic monomer having an alkyl group has a glass transition temperature of the homopolymer of -50°C or lower.

8. The pressure-sensitive adhesive film according to claim 7, wherein the monomer mixture contains a mixture of n-butyl acrylate and 2-ethylhexyl acrylate as the (meth)acrylic monomer having an alkyl group.

9. The adhesive film described in claim 1, wherein the weight average molecular weight of the (meth)acrylic copolymer is 1,000,000 g / mol to 1,300,000 g / mol.

10. The adhesive film described in claim 1, wherein the (meth)acrylic oligomer has a weight average molecular weight of 10,000 g / mol to 40,000 g / mol and a glass transition temperature of 30°C to 40°C.

11. The adhesive film described in claim 1, wherein the content of the trifunctional or higher isocyanate-based curing agent is 0.001 to 0.1 parts by mass per 100 parts by mass of the (meth)acrylic copolymer.

12. The pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic oligomer has a hydroxyl group.

13. The pressure-sensitive adhesive film according to claim 1 , wherein the (meth)acrylic oligomer contains a structural unit derived from a (meth)acrylic monomer having a homopolymer glass transition temperature of 90° C. or higher.

14. The pressure-sensitive adhesive film according to claim 13, wherein the (meth)acrylic monomer comprises at least one selected from the group consisting of methyl methacrylate, methacrylic acid, and tert-butyl methacrylate.

15. The composition further comprises a metal chelate curing agent; The pressure-sensitive adhesive film according to claim 1 , wherein the metal chelate curing agent is contained in an amount of 5 parts by mass or less based on 100 parts by mass of the (meth)acrylic copolymer.

16. The adhesive film according to claim 1 , wherein the adhesive film has a thickness of 20 μm or less.

17. An optical member comprising the pressure-sensitive adhesive film according to any one of claims 1 to 16.

18. An optical display device comprising the pressure-sensitive adhesive film according to any one of claims 1 to 16.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive composition and pressure-sensitive adhesive sheet

    JP2011157458A

  • Adhesive composition and adhesive sheet

    JP2011162593A

  • Adhesive composition, adhesive sheet and laminated sheet for optics

    JP2013018871A

  • Polarizing plate and method for manufacturing the same

    JP2013072951A

  • Adhesive sheet

    JP2016102195A